STRATEGI PENGEMBANGAN EKONOMI UNGGULAN DI DISTRIK TIOM KABUPATEN LANNY JAYA - Nopia Kogoya; Arung Lamba; Dewi Ana Rusim (Magister Perencanaan Wilayah dan Kota Universitas Cenderawasih, 2022)
This study aims to identify the leading economy in Tiom District, Lanny Jaya Regency, choosing a priority strategy to develop the superior product center. This research was conducted with descriptive qualitative research methods, and determined the priority of leading economic development strategies with the SWOT analysis method. Qualitative methods are used to identify internal and external factors that influence the development of leading IKM centers. The results of the study indicate that there are a number of problems that have made the Tiom district unable to develop into a regional superior economic area, such as the absence of regulations regarding the spatial use system for regional superior economic development, then the quality of local population human resources is still minimal to be able to become a driving force in regional economic development. Therefore, the strategy that needs to be developed is to arrange strategic locations so that the development of the agricultural, trade, business and service sectors. Then maximize support from the government and the private sector in terms of developing the people's economy as well as for regional development. Then there needs to be special attention for local human resources to get technical guidance, training, socialization, and assistance to become the front line in driving the regional economy.